REALITAS JIWA SEBAGAI BASIS ONTO-EPISTEMOLOGI PENGALAMAN RELIGIUS: PERSPEKTIF FILSAFAT JIWA ALḤIKMAH MUTA‘ĀLIYAH - Imandega Muhammad (Sekolah Tinggi Agama Islam Sadra, 2020)
A religious experience in the neuroscience view is interpreted as a symptom of neurological disorders of the brain. The neuroscience view is one of the various views that deny the reality of religious experience. Through empirical research instruments, neuroscientists have found that the soul is identical to the brain, which means that every activity can be measured through the brain. This has implications for the experiences of the Prophets in receiving revelations as the result of brain disorders. This paper seeks to explain religious experience through its ontological basis, namely the existence of immaterial existence and the existence of the soul, as well as its epistemological basis, namely the performance of the faculty of knowledge, both of which cannot be separated. The research method used is descriptive-analytic with the philosophical approach of the soul of Al-Ḥikmah Muta’āliyah. The results of this study indicate that the Al-Ḥikmah Muta’āliyah which was founded by Mulla Ṣadrā proves the existence of the wujūd levels, including the soul, explaining the various levels of perception carried out by the soul corresponding to the various levels of existence. Ṣadrā thought can explain the concept of the soul as an immaterial substance that can perceive metaphysical objects as the emanation of God.